Folk music and modern sound - Ferris, William R.; Hart, Mary L. (Center for the Study of Southern Culture series., 1982)
The essays in this collection range from the impact of technology on the British folksong revival to regional characteristics of early rock and roll in New Orleans. Attention is given to the blues, Sacred Harp singing, ethnic music, both black and white gospel, country music, and the polka. Other essays consider the relationship of music from the Yiddish-American theater with that of Broadway, the wide influence and commercialization of black music in today's popular music, myths about early black music, and Charles Ives as folk hero. Contributors include Amiri Baraka, Doris J. Dyen, Dena J.E.